Design of a switched‐capacitor boost converter utilizing magnetic coupling with capability of right‐half plane zero elimination. Issue 1 (30th December 2020) - Goudarzian, Alireza; Mirzaeian Dehkordi, Behzad; Abjadi, Navidreza; Adib, Ehsan
Abstract: The dynamic operation of the conventional boost converters is limited in the continuous conduction mode, due to the presence of at least one right‐half plane (RHP) zero in their control transfer function which can limit the open‐loop bandwidth of the converter. This problem complicates the control design for the output voltage regulation and conversely influences the closed‐loop system stability. To cancel this problem, a new step‐up boost converter using the magnetic coupling and the switched capacitor (SC) is presented. In the proposed converter the effect of the RHP zero can be successfully eliminated, the voltage transfer ratio can be enhanced and the circumstances are provided to reach a small operating duty cycle as well as stress reduction of the diodes and power switch. Using the averaging technique, the state‐space model of the converter is analytically studied and the essential conditions are given for achieving a minimum‐phase structure. Based on the mentioned advantage, a simple classical PI controller for the output voltage regulation is designed. To confirm the theoretical analysis of the proposed converter, simulations and practical results are presented. Also, the performance of the proposed converter is compared with the other boost converters without RHP zero.